Reabilitação do Património Edificado Corrente. Estratégias de Intervenção na Casa Burguesa do Porto - Joaquim Augusto Ferreira Pimenta de Almeida (2014)
The Bourgeois House of Porto is an invaluable typology within the current built heritage, in Portugal. Although this way of building is dominant in the City it has not received the dignification it deserves. Nowadays, despite the considerable number of ongoing interventions, there are lots of decay buildings, showing a high degree of negligence, consequence of abandon or lack of maintenance. Owing to this concerned situation, arised the idea, by the public opinion, that every intervention were an added value. However, the multiplicity of unskilled interventions, that are now prevalent in the City, has resulted in loss of character and the destruction of the essential values of the houses. Given this situation, it is essential to analyze and disseminate ways to safeguard the architectural and constructive values of this typology. In this Dissertation, I intend to highlight the contribution of intervention Strategies, informed by theoretical consensus set out in international documents, to the goal of heritage conservation. Strategies, which are key in the intervention process, are an asset capable of halting this downward spiral, as long as the clarification of decisions is premised on the application of Principles. In order to contextualize and support what I propose to briefly attest in this Dissertation, it was considered extremely important to conduct an evolutionary synthesis of the functional and constructive typology of Porto's Bourgeois House, as well as an analysis of the concepts and theories, targeted towards the current built, embodied in international documents. The insufficient actions of public institutions regarding the heritage's safeguard, as well as the absence of Strategies and the application of Principles in the intervention, motivated this study persecution. From a selection of three exemplary Case studies of interventions in Porto's houses, I seek to validate the importance of the Principles in the intervention process in these buildings. The analysis of Case studies faced with the Theories of heritage safeguard, demonstrated the value and universality of the Principles embodied in international documents, as well as its applicability to the concrete case of Porto's Bourgeois House.